Evaluating Eye Drop Instillation Technique and Its Determinants in Glaucoma Patients. (8th April 2018) - Gao, Xinbo; Yang, Qiongman; Huang, Wenmin; Chen, Tingting; Zuo, Chengguo; Li, Xinyan; Gao, Wuyou; Xiao, Huiming
Abstract : Aim . To evaluate eye drop instillation technique and to explore its determinants in glaucoma patients. Methods . One hundred and thirteen patients diagnosed with glaucoma and self-administering topical antiglaucoma eye drops for at least 1 month were evaluated. All patients instilled artificial tear solution in one eye as they would do at home. The whole process was evaluated by two study staff. A comprehensive score system associated with eye drop instillation techniques was used to quantify the instillation technique and explore its determinants such as demographic and clinical characteristics. Results . Half of the patients (48.67%) finished the administration of eye drop on first attempt.1.7 eye drops were squeezed out on average. 43 patients (37.17%) got contact with ocular surface or adnexa. Only 19.7% patients had eye drop instillation techniques being defined as well. 11 patients (9.7%) had prior instruction regarding using eye drops, while only 4 patients knew to occlude the tear duct by pressing the dacryocyst area. Older age and worse visual acuity were found to be independent risk factors for worse instillation technique. Conclusions . Eye drop instillation technique in glaucoma patients deserves great attention from eye care practitioners during their lifelong follow-up, especially those aged older and have worse visual acuity.